Pan-cancer analysis of GJB5 as a novel prognostic and immunological biomarker - Xiaojuan Yang; Xunjie Cao; Qing Zhu; Hong Wu (Scientific Reports)
Abstract Gap junction protein B5 (GJB5, also known as Connexin 31.1) has recently been reported to be downregulated in several cancer types, where it functions primarily as a tumor suppressor in cancers such as melanoma and non-small cell lung cancer (NSCLC). However, there no reports describing its prognostic and immunological roles in pan-cancer. This study evaluated the association of GJB5 in various cancer types by a comprehensive pan-cancer analysis. The differential GJB5 expression in tumor and adjacent tissues acquired from The Cancer Genome Atlas (TCGA) databases was compared. Furthermore, univariate Cox regression and Kaplan-Meier survival analyses were performed to assess the influence of GJB5 on the disease-specific survival (DSS), disease-free interval (DFI), clinical stage, progression-free interval (PFI), and overall survival (OS) in various cancers. Moreover, the levels of GJB5 and its activity in the tumor microenvironment were assessed via the Tumor Immune Single-cell Hub (TISCH). In addition, the biological importance of GJB5 levels in various cancers was further assessed via Gene Set Enrichment Analysis. Tumor-Immune System Interactions Database (TISIDB) and Tumor Immune Estimation Resource Database 2.0 (TIMER2.0) tools indicated that GJB5 affected the tumor’s immune infiltration potential. This research also evaluated the association of GJB5 with immune features: immune modulatory genes, tumor mutational burden (TMB), and microsatellite instability (MSI). The data indicated that enhanced GJB5 level was linked to worse DFI, OS, PFI, and DSS in some cancers. Additionally, GJB5 level was positively related to immune modulatory genes, TMB, immune cell infiltration, immunological checkpoints, and MSI in malignancies. Furthermore, our study demonstrated that GJB5 was upregulated in colorectal cancer tissues compared to normal tissues. We also assessed GJB5 expression across various pancreatic cell lines. Notably, GJB5 was highly expressed in pancreatic cancer cells relative to normal pancreatic epithelial cells. Additionally, GJB5 knockdown in pancreatic cancer cells resulted in a significant reduction in cell proliferation. In summary, the findings indicated the potential of GJB5 as a prospective prognostic indicator and immunological biomarker.